Potential of Carbon-Chitosan Composite as Biosorbent of Heavy Metal Cu(II) - Bertha Mangallo (FMIPA Universitas Papua, 2022)
This research focuses on adsorption technology from natural sources (biosorbents), esspecially optimizing the potential of composites chitosan as biosorbents for heavy metal waste . The target to be achieved from this research is to obtain the technology of synthesis carbon-chitosan composites for adsorption Cu(II) metal. The study of the characteristics of the chitosan composite with FT-IR, while the adsorption capacity was determined by AAS. The research stages include the isolation of chitin from shrimp shells, deasetilation of chitin into chitosan, the synthesis of charcoal from palm shell, the synthesis of the carbon–chitosan composite (KCK), and the characterization and study adsorption of the chitosan composite on Cu(II) metal. The results of the analysis of the adsorption capacity of chitosan composites showed that formulation of Carbon-Chitosan (KCK) which gave the greatest adsorption toward Cu(II) metal was at a ratio of 1:10 (w/v), which was 2.3037 x 10-4 mol/ g.